UZBEK CONTRIBUTIONS TO SPEECH ACT THEORY: A SYNTHESIS OF RESEARCH TRENDS AND INNOVATIONS (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article explores central issues in pragmatics, focusing on speech act theory as investigated by Uzbek linguists. The primary aim is to synthesize the scholarly contributions of researchers active in Uzbekistan over the past two decades, particularly in the field of speech acts. The study traces the development of speech act theory and examines its application to the analysis of linguistic elements in the Uzbek language, with special attention to culturally embedded expressions and communicative functions. Comparative research highlights both similarities and differences in the realization of speech acts across Uzbek and other languages, emphasizing pragmatic features. Special consideration is given to translation challenges, as pragmatic mismatches can result in shifts in meaning, politeness strategies, and cultural nuances.